(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to map the thematic development of research on Problem-Based Learning (PBL) in the context of Visual Communication Design (VCD) education linked to critical thinking and visual/creative thinking over the period 2015–2025, while identifying potential areas for research novelty. A bibliometric approach was employed by retrieving data using Publish or Perish (PoP) with Google Scholar as the data source and the following query: ("problem-based learning" OR "PBL") AND ("critical thinking") AND ("visual thinking" OR "creative thinking") AND ("visual communication design" OR "graphic design education" OR "design education"). Retrieved metadata were exported in .RIS format and analyzed using VOSviewer to generate term-mapping visualizations, including density, network, and overlay maps. The results indicate a corpus of 500 documents with 11,988 citations, an average of 23.98 citations per paper, and impact indices of h-index = 52 and g-index = 99. VOSviewer mapping shows “critical thinking” as the most dominant and central node, surrounded by pedagogical implementation and design terms such as implementation, model, and effect, as well as educational context terms including teaching, teacher, and higher education. The terms technology and collaboration also appear connected within the network, while visual-creative outcome terms such as creative thinking ability and students’ creative thinking emerge as part of the thematic structure. Overall, these findings suggest that the retrieved research landscape is strongly centered on critical thinking and pedagogical implementation, with notable links to higher-education contexts and technology–collaboration supports.